The role of antibiotics and antibiotic resistance in nature - Rustam I. Aminov (Environmental Microbiology, 2009)
Summary Investigations of antibiotic resistance from an environmental prospective shed new light on a problem that was traditionally confined to a subset of clinically relevant antibiotic‐resistant bacterial pathogens. It is clear that the environmental microbiota, even in apparently antibiotic‐free environments, possess an enormous number and diversity of antibiotic resistance genes, some of which are very similar to the genes circulating in pathogenic microbiota. It is difficult to explain the role of antibiotics and antibiotic resistance in natural environments from an anthropocentric point of view, which is focused on clinical aspects such as the efficiency of antibiotics in clearing infections and pathogens that are resistant to antibiotic treatment. A broader overview of the role of antibiotics and antibiotic resistance in nature from the evolutionary and ecological prospective suggests that antibiotics have evolved as another way of intra‐ and inter‐domain communication in various ecosystems. This signalling by non‐clinical concentrations of antibiotics in the environment results in adaptive phenotypic and genotypic responses of microbiota and other members of the community. Understanding the complex picture of evolution and ecology of antibiotics and antibiotic resistance may help to understand the processes leading to the emergence and dissemination of antibiotic resistance and also help to control it, at least in relation to the newer antibiotics now entering clinical practice.